ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN LISTRIK PRABAYAR DI KELURAHAN TUAH KARYA - trisnawati, Fenny Trisnawati Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was conducted to examine the effect of quality of service for customer satisfaction. The population used in this study there are 12.621 customer using prepaid electricity in Tuah Karya, the sample in this study were 96 customer, type of data used is qualitative data. Data analysis technique using multiple linear analysis, t test and f test with significance level of 0.05%.The result showed that the dimentions of service quality (tangibel,reliability,responsiveness,assurance,and empathy) affect the customer satisfaction. Based on the partial results of the study showed tangibel of positive and significant effect on the customer satisfaction, responsiveness of positive and significant effect on the customer satisfaction, reliability of positive and significant effect on the customer satisfaction, assurance of positive and significant effect on the customer satisfaction,and empathy of positive and significant effect on the customer satisfaction. The coefficient of determination shows that quality of service affect 84,4% and the remaining 15,6% are not described in this research model.Keywords : quality of service,customer satisfaction